Mn-substituted perovskites RECoxMn1-xO3: a comparison between magnetic properties of LaCoxMn1-xO3 and GdCoxMn1-xO3 - Barahona, P.; Gil, V.; Moure, C.; Pecchi, G.; Campos, C.; Peña, O. (Boletín de la Sociedad Española de Cerámica y Vidrio, 2008)
Cooperative phenomena constitute important mechanisms to explain the magnetic properties of the perovskite manganites REMnO3, in which the rare-earth and/or Mn is partially replaced by divalent elements. In this way, the manganese ion changes its valence state (Mn3+ Mn4+), triggering strong magnetic interactions. In this work we describe the case of GdCoxMn1-xO3 (0.0 ≤ x ≤ 1.0) for which the antiferromagnetic interaction between the Gd sublattice and the Mn/Co network leads to a reversal of the magnetic moment at low temperature. No inversion is observed for the LaCoxMn1-xO3 series, in which the ordering temperature may attain a maximum of 235 K for LaCo0.50Mn0.50O3, while it is only 120 K for similar Co/Mn ratio in the case of GdCo0.50Mn0.50O3. Magnetic properties are described in terms of two regimes: one, for x < 0.5, when Co substitutes Mn in the GdMnO3 manganite and another one, for x > 0.5, when Mn substitutes Co in the GdCoO3 cobaltite, while the magnetic interactions are maximized at x(Co) = 0.50. This hypothesis is discussed in terms of the respective oxidation states of both manganese (Mn3+ / Mn4+) and cobalt (Co2+ / Co3+). El fenómeno cooperativo constituye un importante mecanismo para explicar las propiedades magnéticas de las perovskitas manganitas TRMnO3, en las que el catión de tierra rara, TR, y/o el catión Mn3+ son parcialmente reemplazados por cationes divalentes. Por esta vía el ión de manganeso cambia de estado de valencia (Mn3+ Mn4+), generando fuertes interacciones magnéticas. En el presente trabajo se describe el caso de las soluciones sólidas GdCoxMn1-xO3 (0.0 ≤ x ≤ 1.0) para las que la interacción antiferromagnética entre la subred del Gd3+ y la red Mn/Co lleva a una inversión del momento magnético a baja temperatura. No se ha observado inversión para la serie LaCoxMn1-xO3, en que la temperatura de orden puede alcanzar un máximo de 235K para LaCo0.50Mn0.50O3, mientras que en el caso de GdCo0.50Mn0.50O3, en que sí se observa inversión, la temperatura de orden es sólo de 120 K para una razón Co/Mn similar. Las propiedades magnéticas se describen en términos de dos regímenes diferentes: uno, para x < 0.5, cuando Co sustituye al Mn en la manganita GdMnO3 y otro, para x > 0.5, cuando Mn sustituye a Co en la cobaltita GdCoO3. Las interacciones magnéticas se maximizan a x(Co) = 0.50. Esta hipótesis se discute en términos de los respectivos estados de oxidación de ambos cationes: manganeso (Mn3+ / Mn4+) y cobalto (Co2+ / Co3+).